Ogólna charakterystyka procesów prywatyzacji w gospodarce brytyjskiej w latach osiemdziesiątych - Klich, Jacek (Wydział Prawa i Administracji UAM, 1991)
In the article, the main features of the privatisation in the United Kingdom during 80s are presented. The Author initially describes the origin, the concept and the main aims of the transformation in the ownership in the British economy under conservative power between 1979-1990. Subsequently, the typical phases of the process of privatisation are represented. In the second part of the article some economic, social and political results of the process of privatisation are shortly considered. Finally, the Author undertakes an attempt to compare the privatisation in the UK with the process of the reform in the ownership structure which is actually being initiated in the Polish economy. In the conclusions section, the list of the main similarities and differences between the countries in question are presented.
General characteristic of the process of privatization in the UK economy in the 1980s